Los guisantes maravillosos - Bofill, Francesc; Ballester, Arnal (Barcelona : La Galera, 1993)
A retelling of Jack and the beanstalk.
Keywords: Giants -- Fiction; Fairy tales; Fairy tales; Folklore -- England; Giants -- Fiction; Spanish language materials; Fairy tales; Giants; Fiction